A nationwide, population-based, long-term follow-up study of repeated self-harm in Taiwan - Chung Chi-Hsiang; Lai Ching-Huang; Chu Chi-Ming; Pai Lu; Kao Senyeong; Chien Wu-Chien (BMC, 2012)
Abstract Background Previous follow-up studies of repeated self-harm show that the cumulative risk of repeated self-harm within one year is 5.7%-15%, with females at greatest risk. However, relatively few studies have focused on the Far East. The objective of this study was to calculate the cumulative risk of repeated self-harm over different lengths of follow-up time (3 months, 6 months, and 1-8 years), to determine factors influencing repeated self-harm and to explore the interaction between gender and self-harm methods. Methods We used self-harm patient who hospitalized due to first-time self-harm between 2000 and 2007 from 1,230 hospitals in Taiwan. Hospitalization for repeated self-harm among members of this cohort was tracked after 3 months, 6 months, and 1-8 years. Tracking continued until December 31, 2008. We analyzed the cumulative risk and risk factors of repeated self-harm by using negative binomial regression. Results Of the 39,875 individual study samples, 3,388 individuals (8.50%) were found to have repeatedly self-harmed. The cumulative risk of repeated self-harm within three months was 7.19% and within one year was 8%. Within 8 years, it was 8.70%. Females were more likely to repeatedly self-harm than males (RR = 1.21, 95% CI = 1.15-1.76). The main method of self-harm was solid or liquid substances (RR = 1.88, 95% CI = 1.23-2.04) or cutting or piercing (RR = 1.36, 95% CI = 1.02-1.82), and in patients with psychiatric disorders were more likely to self-harm (RR = 1.61, 95% CI = 1.48-1.75). Conclusions The key time for intervention for repeated self-harm is within three months. Appropriate prevention programs should be developed based on gender differences.